2016
DOI: 10.1007/s00417-016-3554-0
|View full text |Cite
|
Sign up to set email alerts
|

Binocular function changes produced in response to overnight orthokeratology

Abstract: OK induces minimal changes in the binocular function for either short-term or long-term periods, apart from a near exophoric trend over the short-term period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…96,290 Multifocal contact lenses worn by children can induce exophoria, increasing with accommodative demand. 79 OK causes minimal effects on ocular alignment, 291 and a link between OK or pharmacological treatments for myopia control has not been reported. These results indicate some potential benefit of monitoring heterophoria either upon inclusion in a study or during the course of the study.…”
Section: Lag Of Accommodationmentioning
confidence: 99%
“…96,290 Multifocal contact lenses worn by children can induce exophoria, increasing with accommodative demand. 79 OK causes minimal effects on ocular alignment, 291 and a link between OK or pharmacological treatments for myopia control has not been reported. These results indicate some potential benefit of monitoring heterophoria either upon inclusion in a study or during the course of the study.…”
Section: Lag Of Accommodationmentioning
confidence: 99%
“…However, for this study, this limitation should have no impact when comparing the response in different times of the treatment, and as mentioned in the Section 2, it is not expected that under the conditions of this experiment, the response would be significantly different. Despite the results presented by Felipe-Marquez et al [51], who showed that OK does not significantly change the binocular function for either short-or long-term periods, in a further investigation, it would be interesting to evaluate the accommodative response with the same method and with a larger sample size, subjects with different degrees of myopia, and a long-term group. Batres et al recently evaluated the changes in accommodative LAG using Nott retinoscopy and concluded that there was a reduction of about 0.25 D in accommodative lag from baseline [52].…”
Section: Discussionmentioning
confidence: 85%
“…First, human neuroadaptation can compensate for optical alterations with time goes [ 27 30 ]. In addition, previous studies, which investigated lenses designed with peripheral myopic defocus, have evaluated binocular vision and accommodation at the baseline and found that fusional vergence [ 31 ], phoria [ 31 34 ], NPC [ 32 ], AA [ 31 , 35 ], AR [ 31 , 35 , 36 ], and AF [ 33 , 35 , 36 ] did not change with time. Based on these evidences, the long-term influence may keep consistent with that of short term if extending boldly.…”
Section: Discussionmentioning
confidence: 99%